Acceptance of a net zero urban water future: challenges and strategies for a sociotechnical shift of water systems - Crosson, Courtney; Pincetl, Stephanie; Bhushan, Rashi; Scruggs, Caroline; Zuniga-Teran, Adriana; Gupta, Neha; Porse, Erik; Sharvelle, Sybil; Boccelli, Dominic L.; Pierce, Gregory; Schuler, Andrew; MacAdam, James; et al. (Frontiers in Water, 2025)
The Colorado River supplies over 40 million people in the United States Southwest with their daily water supply and is currently unable to meet these demands. Faced with the challenges of climate change, population growth, and aged infrastructure, urban water systems in the Southwest, as sociotechnical systems, will need to evolve to become more sustainable. A Net Zero Urban Water (NZUW) approach meets the needs of a given community with a locally available and sustainable water supply, without detriment to interconnected systems and long-term water supply. Transitioning to a NZUW future will require considerable changes related to water availability, sources, technology, management, costs, and the urban landscape. Acceptance of these changes is key to a successful sociotechnical shift in urban water systems in the arid Southwest. Our results identify three main actors (institutions, civil society, and the public) and five key factors (public trust, perceived issue severity, infrastructural inertia, cultural preferences, and cost) that influence acceptance of change across the urban water system. Under each factor, we identify strategies that have been used to influence acceptance by each of the three actors (e.g., transparent communication, community engagement, inter-agency collaboration, advocacy campaigns, and financial incentives). To better understand acceptance of the changes necessary for a NZUW future, we examined four case study cities across the Colorado River System to illustrate the dynamics between the identified actors, factors, and strategies: Albuquerque, Denver, Los Angeles, and Tucson. Our results highlight that fostering public trust and understanding, overcoming institutional and cultural barriers, and aligning financial policies are key for advancing a NZUW future. We conclude that cities in the Southwest are in the middle of significant sociotechnical shifts toward greater water system sustainability. Acceptance of these changes by institutions, civil society, and the public continues to be critical, particularly for a NZUW future to be realized.